Bismuth Nanoparticles Encapsulated in Nitrogen‐Rich Porous Carbon Nanofibers as a High‐Performance Anode for Aqueous Alkaline Rechargeable Batteries. Issue 7 (3rd December 2021) - Zhou, Kai; Wang, Shuai; Guo, Xinying; Zhong, Guixiang; Liu, Zhenbang; Ma, Yingming; Wang, Haoyu; Bao, Yu; Han, Dongxue; Niu, Li
Abstract: The aqueous alkaline rechargeable batteries (AARBs) have an attractive potential for electrochemical energy storage devices. In view of the advantages of high theoretical capacity and desirable negative operating window, bismuth (Bi) has been deemed as a hopeful anode material for AARBs. Unfortunately, intensive reported works of Bi anode are still confronted with limited capacity and poor cycling stability. Herein, the designed electrodes of different size Bi nanoparticles embedded in porous carbon nanofibers with a contrasting nitrogen doping content are obtained by electrospinning and thermal treatment processes. The effect of the N dopant in carbon shell is demonstrated on the Bi core, which is in favor of enhancing the capacity of Bi anodes. More importantly, the core structure with highly dispersed ultrasmall Bi nanoparticles (<20 nm) in carbon matrix plays a crucial role in long‐term durability. Accordingly, the optimized polydisperse ultrasmall Bi nanoparticles confined in N‐rich porous carbon nanofibers electrode (Bi@NPCF) presents an admirable capacity of 196.1 mAh g −1 at 3 A g −1 and outstanding durable lifespan (retain 116.95% after 10 000 cycles). In addition, the fabricated Bi@NPCF//NiCo2 O4 battery exhibits an exceptional energy and power density with durable stability (95.9% after 5000 cycles). Abstract : The effects of the N‐doped carbon shell and the size of Bi core on the performance of Bi anodes for aqueous alkaline rechargeable batteries are verified by electrospinning synthesis of Bi nanoparticles encapsulated in N‐doped carbon nanofibers.